Analysis of photobiomodulation associated or not with platelet-rich plasma on repair of muscle tissue by Raman spectroscopy - Ozaki, Guilherme Akio Tamura; Camargo, Regina Celi Trindade [UNESP]; Koike, Tatiana Emy [UNESP]; Garcia, Thiago Alves [UNESP]; Castoldi, Robson Chacon; Pereira, João Domingos Augusto dos Santos [UNESP]; Constantino, Carlos José Leopoldo [UNESP]; Camargo Filho, José Carlos Silva [UNESP] (Springer Nature, 2016)
Treatment of muscle injuries usually results in the interruption of sports practice; thus, studies aimed at accelerating the return to activity, with proper tissue repair, are important. Therefore, this study aimed to evaluate the effects of photobiomodulation (PBM), associated or not with platelet-rich plasma (PRP), on the treatment of muscle injury. Thirty-five animals were used and divided into five groups (n = 7): control (C), control lesion (CL), lesion treated with low-level laser therapy (LLLT) (LLt), lesion treated with PRP (LP), and lesion treated with both techniques, LLLT and PRP (LLtP). Muscle injury was induced by stretching the gastrocnemius muscle, and the animals in the LLtP and LP groups received the application of PRP immediately following the injury. The LLLT was applied daily for 7 days. The animals were euthanized 7 days after the injury. Analysis of the NADH/NAD ratio and collagen was performed by Raman spectroscopy; in addition to which, histological analysis of the gastrocnemius muscle was performed. The LLtP group demonstrated a reduction in the area of injury, regenerating cells and a healthy appearance of muscle fibers. The Raman analyses showed a reduction in the NADH/NAD ratio in the CL group, demonstrating oxidative stress, and the collagen presented a reduction in the CL and LLt groups, when compared with the C group. It is concluded that either PBM or PRP, and the association of both, was able to reduce the oxidative stress promoted by injury and modulate collagen production at the site of the injury. Furthermore, although both treatments individually were effective for repairing the damage caused by muscle injury, the association of both demonstrated a better histological aspect.
Keywords: Injury; Low-level laser therapy; Platelet-rich plasma; Raman spectroscopy; Skeletal muscle